What is Raḥmat li al-ʿĀlamīn for IIUM? - Muhsin, Sayyed Mohamed (Mission Soft Foundation, 2021)
Following the Prophetic path can be accomplished at various levels, like an individual, familial, institutional; and its pinnacle is when Ummah at large altogether takes up this mission, which then fulfils the Quranic praise, “You are indeed the best community that has ever been brought forth for [the good of] mankind” (Āl-ʿImrān: 110). This write-up is a modest attempt to look into the aspect when this mission is executed at a university level in the context of International Islamic University Malaysia (IIUM).